Pelatihan Gerakan Tari Kreasi Dalam Meningkatkan Keterampilan Menari Siswa Kelas V SDN 28 Mataram - Chairunnisa, Lulu; Alifia Rahman, Najwa (Universitas Mataram, 2024)
Dance is an effective art form for increasing students' creativity. Creativity in dance is an educational tool that is useful for expressing emotions and expressions in creativity. This service activity is carried out in class V or high class using methods in the form of observing, trying and practicing. This method is the process of students understanding the dance movements taught by the teacher or educator. In the process of implementing service activities, there are 3 stages that must be carried out, namely the planning/preparation stage, the implementation stage and the reflection stage. The creative dance movement training activity that was carried out included 5 students who took part in the activity from start to finish. The training was carried out in three meetings. The training activities went according to expectations and objectives and received a good and positive response from the entire school community.